Embedding Bachelor of Engineering University Education with Enhanced Work-Integrated Learning - Pradeep Vailasseri; John M. Long; Matthew Joordens (MDPI AG, 2021)
A study on the effectiveness of engineering education in the development of industry-ready graduate engineers was conducted among academics and industry experts of engineering disciplines who have relevant experience in work-integrated learning in Australia. The hypothesis was that embedding enhanced work-integrated learning into all study semesters has the increased possibility of developing industry-ready graduate engineers. This paper outlines the research outcomes and an enhanced work-integrated learning framework that might be helpful for improving the industry-readiness of graduating engineers. Based on the research results, the researchers propose the allocation of an appropriate level of work-integrated learning for each indicator of attainment component from the elements of Engineers Australia's Stage I Competencies. The aim of this paper is to provide detailed recommendations for implementing an enhanced work-integrated model in Bachelor of Engineering programs in Australia. The authors also present the concept of curriculum development based on industry-integrated learning outcomes, as well as the campus and industry engagement model for enhanced work-integrated learning for the subjects of study in the Bachelor of Engineering program. This framework can be used globally as a reference for developing similar work-integrated learning models.